Media-social behavior of Muhammadiyah members in China in the framework of Alexander Wendt's international communication constructivism - Dani Fadillah; Uspal Jandevi (Journal of Social Studies (JSS), 2020)
This paper aims to determine how the social media behavior carried out by Muhammadiyah members in China after the Chinese government's viral repressive action towards the Uighur ethnic minority in the Xinjiang region. As an Islamic-based social organization, and even more geographically, both live in China, the Head of the Special Branch of Muhammadiyah China, the Nanjing Regional, certainly has its study regarding the issue which may have a different point of view from the views of most Indonesians on this matter and take action. to respond of the news that, the response of most Indonesians after the virality of the issue. Therefore, the author tries to explain how Muhammadiyah members' media behavior in China and their opinions to build amid Indonesian society after the viral news above uses constructivism logic developed by Alexander Wendt. This paper's conclusion shows that there are efforts by Muhammadiyah cadres in China to calm the heating up the domestic atmosphere as a form of creating a more conducive atmosphere between China and Indonesia.